Studi Tentang Peran Advokat Dalam Sistem Peradilan Dan Penegakan Hukum - Salmah, Andri Nurwandri, Arbi Aulia, Dani Sapitri, Dwi Erikha, Mutmainnah Butar Buta, Richa Fitri Me (CV. PUSDIKRA MITRA JAYA, 2024)
This research aims to understand what the role of advocates is in the justice system and law enforcement. The approach used in the research here is qualitative. The method used to collect information is through interviews. The data analysis process in this research is descriptive. The findings from this research state that advocates are considered law enforcers and are a profession that has freedom, independence and responsibility in carrying out their duties to enforce the law as regulated by law. In Law Number 18 of 2003 concerning Advocates, Advocates play a role in providing services for handling a case requested by their client, and in handling their duties there are non-litigation and also litigation ones. What is meant by litigation is in court and non-litigation is outside of court. In Indonesia, there are four justice systems which include General Courts, Religious Courts, State Administrative Courts, and Military Courts. The judicial system refers to all processes or procedures carried out in court, which involve examination, decision and trial of a case by applying the law.